Vitamin D status of patients visiting a private endocrinology clinic: a retrospective analysis from Karachi, Pakistan - Ahsan, Tasnim; Ghaus, Saima; Sohail, Erum; Aijaz, Wasfa; Uzma Erum; Samar Abbas Jaffri (Journal of the Pakistan Medical Association, 2024)
Objective: To estimate the burden of vitamin D deficiency and its association with chronic diseases in patients visiting a private endocrinology clinic in an urban setting. Method: The retrospective study was conducted at the Medicell Institute of Diabetes Endocrinology & Metabolism, Karachi, and comprised medical records of adult patients of either gender between January 2000 and December 2019.Vitamin D status of the patients and its association with various chronic disorders were investigated. Data was analysed using SPSS 21. Results: Of the 2,854 patients with mean age 40.87±15.1 years, 2,302(80.7%) were females, and 552(19.3%) were males. There were 1055(37%) patients with vitamin D deficiency, 1,040(36.7%) with severe deficiency, 462(16.2%) with insufficiency, 295(10.3%) with normal status, and 2(0.1%) with vitamin D toxicity. Vitamin D deficiency was observed more frequently in those aged<40 years, and the deficiency was significantly related to type 2 diabetes, impaired glucose tolerance, dyslipidaemia and autoimmune disorders (p<0.05). Conclusion: The burden of vitamin Deficiency was found to be alarmingly high at a private endocrine and medicine clinic serving a middle and upper socioeconomic class population in an urban setting. Key Words: Vitamin D deficiency, Metabolic disorder, Diabetes mellitus, Hypertension.